2019
DOI: 10.1002/pbc.27692
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and predictors of therapy abandonment in pediatric central nervous system tumors in low‐ and middle‐income countries: Systematic review and meta‐analysis

Abstract: Background Outcomes of pediatric central nervous system (CNS) tumors in low‐ to middle‐income countries (LMIC) are poorer than their high‐income counterparts. Abandonment of therapy is increasingly recognized as a key contributor to this disparity, but has been poorly quantified. We performed a meta‐analysis to determine the magnitude of abandonment in pediatric CNS tumors in LMIC, and risk factors and interventions aimed at reducing this. Patients and methods We searched seven databases for pediatric CNS tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Venezuela is undergoing special socioeconomic and political instability (37), which may affect the current and future outcomes of childhood leukemia. Other reports have found that abandonment of treatment is a major barrier to successful treatment and remission of the disease in low-and middle-income countries in Central America (13,38,39). Moreover, economic disparities in certain communities within countries likely affect access to health services (34,40).…”
Section: Discussionmentioning
confidence: 99%
“…Venezuela is undergoing special socioeconomic and political instability (37), which may affect the current and future outcomes of childhood leukemia. Other reports have found that abandonment of treatment is a major barrier to successful treatment and remission of the disease in low-and middle-income countries in Central America (13,38,39). Moreover, economic disparities in certain communities within countries likely affect access to health services (34,40).…”
Section: Discussionmentioning
confidence: 99%
“…(i) Refusal and abandonment of therapy: refusal and abandonment of therapy is a major cause of therapeutic failure in countries with limited resources, where children and families incur unaffordable direct and indirect costs of care 18,19 , and affect up to 50-60% of children in some world regions -often exceeding all other causes of treatment failure. 11 Most children abandon early, usually after induction remission in leukaemias or at the time of radical surgeries (e.g.…”
Section: Panel 1: the Child With Cancer In Resource-limited Settingsmentioning
confidence: 99%
“…We extended the Global Childhood Cancer microsimulation model, described in detail elsewhere 56 and briefly in appendix panels 1 and 2 (pp. [16][17][18][19], to project the number of childhood cancer deaths worldwide between 2020 and 2050 for children diagnosed and undiagnosed with cancer.…”
Section: Modelling To Estimate the Number Of Deaths From Childhood Camentioning
confidence: 99%
“…However, childhood leukemia and economic status do not appear to be significantly related in high-income countries such as Switzerland or the US [ 31 , 36 ], suggesting that others factors have contribute to leukemia mortality. For example, some reports found that abandonment of treatment is a major barrier to successful treatment and remission of the disease in low- and middle-income countries [ 14 , 37 , 38 ], which could increase the mortality rates in this population. Although these inequities are plausible explanations for the unremarkable trends seen in our analysis, there is still the need to explore further factors such as environmental hazard or components of the healthcare system, to generate tailored and evidence-based health policies.…”
Section: Discussionmentioning
confidence: 99%